Productive parameters of guinea pigs raised with diets supplemented with fish oil and sacha inchi seeds - Guevara V., Jorge (2017)
The aim of the study was to determine the productive parameters of guinea pigs raised with diets supplemented with fish oil and sacha inchi seeds. Forty eight male guinea pigs of 42 days old were used, with an initial body weight of 615 g. The guinea pigs were randomly assigned to 4 treatments with 3 repetitions (rearing pools) of 4 animals each. Dietary treatments were: T0: Control, T1: diet supplemented with 1.0% fish oil; T2: diet supplemented with 4.0% sacha inchi seed; and T3: diet supplemented with 1.0% fish oil + 4.0% sacha inchi seed. The experimental phase lasted 28 days. Body weight gain, feed intake, feed conversion and carcass yield were evaluated. The average of individual body weight gain ranged between 315 and 353 g per treatment, consumption ranged between 1172 and 1224 g dry matter, feed conversion ranged between 3.53 and 3.73 and carcass yield varied between 69.4 and 71.7% without statistical differences between treatments.